Counterexamples in probability and real analysis - Wise, Gary L., 1945- (Oxford University Press, 1993)
Ideas in mathematical sciences that might seem intuitively obvious may be proved incorrect with the use of their counterexamples. This monograph concentrates on counterexamples for use at the intersection of probability and real analysis, which makes it unique among treatments of counterexamples. The authors maintain that, in fact, if taught correctly, probability theory cannot be separated from real analysis.